APLIKASI JARINGAN SARAF TIRUAN UNTUK EVALUASI VENTILASI BANGUNAN TROPIS LEMBAB - Jefrey Ignatius Kindangen; Sumenge T. Gideon Kaunang; Djangkung Sardjono (DIMENSI (Journal of Architecture and Built Environment), 2001)
In humid tropical climates where the average annual temperature and the relative humidity are high, the air flows in buildings may be enough to provide ventilation at a satisfactory level of comfort without the use of active air-conditioning systems. Air movements have an effect on thermal comfort, decreasing the risk of local overheating, and giving sufficient interior air velocity to improve the evaporation of sweat. Air movements inside a building depend not only on the external wind velocity, but also on a number of architectural parameters. Changes in these parameters can modify interior airflow patterns. However, if a meaningful number of such parameters are to be taken into account, the determination of interior air velocity is very difficult. It was therefore decided to look at how artificial intelligen techniques might facilitate the solution of the problems involved. This article describes an initial attempt to apply artificial neural networks to be used in the evaluation of building ventilation. We used the interior velocity coefficient as an indicator of the performance of building ventilation. The interior velocity coefficient is a measure of the relative strength of the interior air movement in horizontal planes representing an occupied space. It is shown how these ideas are applied in the present research, and the results are presented. The utilization of neural networks as a universal predictor is an interesting subject for investigation and evaluation, given their ability to provide reliable results in situations where a large number of parameters have to be taken into account simultaneously. Abstract in Bahasa Indonesia : Dalam iklim tropis lembab dimana temperatur udara rata-rata dan kelembaban relatif udara yang tinggi, aliran udara dalam bangunan dapat memberikan tingkat kenyamanan tanpa menggunakan sistem pendinginan udara aktif. Aliran udara mempengaruhi tingkat kenyamanan termik dengan menurunkan resiko pemanasan lokal dan memperbaiki tingkat evaporasi keringat. Aliran udara dalam bangunan tidak hanya dipengaruhi oleh kecepatan angin, tetapi juga oleh sejumlah parameter arsitektural. Merubah parameter-parameter ini dapat memodifikasi pola aliran udara dalam ruang. Akan tetapi, apabila sejumlah paramater ini harus diperhitungkan, determinasi kecepatan udara dalam suatu ruangan menjadi sangat sulit. Untuk persoalan tersebut dicoba untuk menerapkan teknik intelijen buatan untuk menyelesaikan masalah ini. Artikel ini menjelaskan tentang penggunaan Jaringan Saraf Tiruan untuk mengevaluasi ventilasi bangunan. Kami menggunakan koefisien kecepatan udara sebagai indikator kinerja ventilasi bangunan. Koefisien ini merupakan suatu ukuran laju aliran udara relatif dalam suatu ruangan pada bidang horisontal dalam ruang hunian. Artikel ini menunjukkan bagaimana ide tersebut diaplikasikan dan hasilnya dipresentasikan. Penggunaan Jaringan Saraf Tiruan sebagai prediktor universal merupakan suatu hal yang menarik dalam investigasi dan evaluasi ventilasi bangunan. Ditunjukkan kemampuannya untuk memberikan hasil yang reliabel dalam keadaan dimana sejumlah besar parameter harus diperhitungkan secara simultan. Kata kunci: aliran udara, jaringan saraf tiruan, koefisien kecepatan udara.